UTILIZING WORDPRESS IN INVESTIGATING ENGLISH FOREIGN LEARNERS’ READING STRATEGIES - Novita Eka Tristiana (INOVISH JOURNAL, 2018)
The purpose of this study is to reveal what kinds the students’ reading strategies. The Participant in this research were the students of third semester of English Education Department of STKIP Muhammadiyah Pringsewu lampung who took Reading 2.  There were 38 students who involved in this research. Since this research used qualitative research design that involved case study, the researcher only took 5 students as the representative of group created by researcher  in order to get rich and deep information. The data collecting technique used in this research were think-aloud protocol, reflective journal that uploaded through wordpress and interview guide for reading strategies.  In analyzing the data, the researcher carried out some activities, namely describing, classifying, and connecting. The research finding obviously describe that the students used three main strategies in reading namely, Cognitive  Reading Strategy, Metacognitive  Reading Strategy and Compensation Reading Strategy.